Virtual Manufacturing as Tool for Material and Process Developments and Optimizations / Marcel Graf ...[et al.] - Graf, Marcel; Härtel, Sebastian; Binotsch, Carolin; Awiszus, Birgit (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Virtual process design based on numerical methods is a tool that has been widely used for years to help estimate expected forces, stresses and temperatures. Current efforts to improve hardware performance also seek to take account of the material itself in the numerical simulation. The necessary models to describe the material flow or microstructural development based on physical or semi-empirical approaches have been implemented to a large degree; however, the significance of the calculation results correlates strongly with the underlying material coefficients. These calculations are often based on the material data found in the reference literature or in material databases, as a process-specific material characterization would be time and cost intensive. There is usually no information about the method of determination (e.g., the type of flow curve), so the publicly accessible data is in principle only useful for an initial approximate calculation. The modelling constructed on the basis – forming behaviour and microstructural behaviour during the forming process – is the current research topic in numerous projects, with the intention of being able to draw conclusions about the mechanical properties in the final component after an FEM calculation. This should ultimately lead to processes and materials being optimized and modified in such a manner that, if the necessary component properties are known, a material-specific process route can be inversely deduced. This paper is intended to provide an overview of selected possible applications of FEM and to identify the potential benefits of having the corresponding material data of the forming blanks.